Manual de funciones para la Modalidad de Estudios a Distancia de la Universidad Nacional de Loja - Torres Cañar, Dennis Ximena (2017)
He present work of research is aligned according to the normative existing, whose title is "FUNCTIONS MANUAL FOR THE MODALITY OF DISTANCE STUDIES OF THE NATIONAL UNIVERSITY OF LOJA", the same that has as target main develop a manual of procedures on the compliance of them activities that allow improve the situation current of this unit academic. For the realization of this research was conducted in the first instance the bibliographical revision, whose topics were related to the subject in question, under the frame of reference and conceptual framework; also used as research methods: scientific, inductive and deductive, analysis, synthesis, and statisticians. Also applied techniques that facilitated obtaining information including interview, survey, observation form, these tools were applied to 41 people, including teachers and employees administrative 1 interview to Mrs. Directora the UED. As regards them results, is can indicate that is presents the information by half of pictures statistical with them due representations graphic of which is deduced that the UED not has with a manual of functions. In the discussion of results was the proposal according to the detected problem, and which has created a manual functions, it has been designed taking into account the Organic Statute of the University, subsequently were established in the conclusions, recommendations and the detail of the literature used for this effect, as well as the respective annexes. Keywords Manual functions, administrative employees, teachers.